Rapid Generation of the Shortest Generalized Dubins Path in Forced Landing - Tian Min; Shi Yingjing; Li Rui; Tlelo-Cuautle Esteban (International Journal of Applied Mathematics and Computer Science)
This paper investigates the problem of rapid shortest path generation during an aircraft’s forced landing, where the heading angle of the target point is variable. To address the minimum turning radius constraint of the aircraft, the shortest path is determined using Dubins curves. Additionally, the shortest generalized Dubins path is selected when the heading angle of the target point is not fixed. Specifically, the paper focuses on four generalized Dubins curves which are relevant to forced landings. By comparing the lengths of these curves, the shortest curve is identified for different positional relationships between the forced landing starting and ending points, with theoretical justifications provided. Additionally, distance calculation methods for these curves are presented to determine the distance of the shortest generalized Dubins path. The effectiveness of the proposed method is confirmed through numerical simulations.